How nurses restore and maintain mobility in hospitalised older people: An integrative literature review. (17th May 2018) - Constantin, Stephanie; Dahlke, Sherry
Abstract : Aim: The aim of this integrative review of the literature was to evaluate and summarise current research about how nurses maintain and improve hospitalised older peoples' mobility levels. Background: Older persons make up the majority of healthcare recipients, and they are at risk to experience significant decline in their mobility once hospitalised. This can result in longer hospitalisations or nursing home admissions. Currently, it is not well understood how nurses maintain and restore mobility of hospitalised older persons. Design: An integrative literature review using key concepts related to hospitalised older people, mobility and nursing care was conducted. Whittemore and Khalf's five‐stage methodological framework for integrative reviews was utilised. Methods: Two reviewers screened 1640 resources from four computerised databases published in English during 2000–2017. Reviewers used the Mixed Methods Appraisal Tool (MMAT) and CASP quality appraisal tools to assess the thirteen included articles. Results: The findings of this review reveal that little is known about how frequently nurses are mobilising, that many nurses perceive mobilising older patients to be physiotherapy's responsibility and that education about mobilisation can improve nurses' willingness to mobilise people. Conclusion: By investing in education and training programmes targeted for nurses, nurses can feel empowered in their ability to mobilise patients and are encouraged to take ownership of their patient's functional needs. In order to facilitate mobility, adequate staffing levels are necessary for transferring and ambulation, mobility assistive devices such as walkers and canes and environments with adequate space to mobilise. More research is needed to better understand and overcome barriers that nurses face in mobilised older people in acute care. Implications for practice: The nursing team can work together to prioritise mobilisation to assist in restoring and maintaining the function of hospitalised older people. Educators could review their mobility programmes to increase graduate nurses' confidence and self‐efficacy in mobility assessments and thus prepare graduate nurses for the realities of practice.